FATIGUE PERFORMANCE OF RECYCLED ASPHALT PAVEMENT REJUVENATED WITH BIO-REJUVENATOR FROM COCONUT SHELL - Sihombing, Atmy Verani Rouly (Jurnal Jalan Jembatan, 2023)
This study investigated the fatigue performance of recycled asphalt mixtures (reclaimed asphalt pavement, RAP) rejuvenated with a bio-rejuvenator derived from coconut shells (BioCS), specifically combinations with 30% RAP using a four-point bending test with strain-controlled and compared the results with the Austroads model. The study found that adding a bio-rejuvenator increased stiffness, reduced cracking, and improved fatigue life, with the optimal dosage of 23% by weight of RA binder (bitumen from RAP). The fatigue life decreased as the strain increased but adding BioCS to AC-WC mixtures containing up to 30% RAP still provided a better fatigue life than the AC-WC control mixture. BioCS is suitable for AC-WC mixtures containing up to 30% RAP in the 200 - 400 με strain classification range. Furthermore, the fatigue failure values generated from laboratory testing using the four-point bending test were close to the Austroads model with a ratio of 0.9. This suggests that the variables from the Austroads model can be considered to build a fatigue life model of asphalt mixtures containing RAP and BioCS as rejuvenators. However, more research is needed to fully understand the long-term performance and environmental impact of using bio-rejuvenators in asphalt mixtures. Overall, this study supports using bio-rejuvenators derived from coconut shells as a sustainable alternative to petroleum-based rejuvenators for improving the fatigue life of recycled asphalt mixtures. Keywords: fatigue life, AC-WC, bio-rejuvenator, coconut shell, recycled material, four-point bending test